Religious and Cultural Contestation in Strengthening The Role of Women Through Pedhalangan Art - Arauf, Muta Ali (Al-Adyan: Journal of Religious Studies, 2024)
This article explores the contestation of religion and culture in the context of female puppeteers in Banyumas. Some young female puppeteers in Banyumas show their talent and interest in Wayang Golek performances performed by the Paguyuban Muda Banyumas to preserve existing local culture. This qualitative research uses data collection techniques through observation and interviews with the chairman and members of the Banyumas Young Dalang Art Association. The results of this study show that the role of women in the arts is interpreted from the point of view of religion and culture, so the dynamics are diverse. Religious and cultural contestation regarding the world of Pedhalangan Art provides ample opportunities for the Banyumas female puppeteer community to be more aggressive in facing the increasingly rampant Islamization fever that often marginalizes local culture, which is sometimes considered traditional and always synonymous with heresy. On the other hand, the phenomenon of female puppeteers played by young women in Banyumas is part of an effort to preserve ancestral culture that is increasingly fading on the surface. At least to preserve local culture, maintain and produce cultural products, create cultural agents, and strive to build national character.Artikel ini mengeksplorasi kontestasi agama dan budaya dalam konteks dalang perempuan di Banyumas. Beberapa dalang perempuan muda di Banyumas menunjukkan bakat dan minat mereka dalam pertunjukan wayang golek yang dilakukan oleh Paguyuban Muda Banyumas untuk melestarikan budaya lokal yang ada. Penelitian kualitatif ini menggunakan teknik pengumpulan data melalui observasi dan wawancara dengan ketua dan anggota Paguyuban Seni Dalang Muda Banyumas. Hasil penelitian ini menunjukkan bahwa peran perempuan dalam seni diinterpretasikan dari sudut pandang agama dan budaya, sehingga dinamikanya beragam. Kontestasi agama dan budaya terkait dunia seni pedhalangan memberikan peluang besar bagi komunitas dalang perempuan Banyumas untuk lebih agresif menghadapi demam Islamisasi yang semakin marak, yang seringkali meminggirkan budaya lokal yang terkadang dianggap tradisional dan selalu identik dengan bid'ah. Di sisi lain, fenomena dalang perempuan yang dimainkan oleh perempuan muda di Banyumas merupakan bagian dari upaya melestarikan budaya leluhur yang semakin memudar di permukaan. Setidaknya untuk melestarikan budaya lokal, memelihara dan menghasilkan produk budaya, menciptakan agen budaya, dan berupaya membangun karakter bangsa.